2008
DOI: 10.1371/journal.pone.0003394
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-Synuclein Fibrillization by Dopamine Is Mediated by Interactions with Five C-Terminal Residues and with E83 in the NAC Region

Abstract: The interplay between dopamine and α-synuclein (AS) plays a central role in Parkinson's disease (PD). PD results primarily from a severe and selective devastation of dopaminergic neurons in substantia nigra pars compacta. The neuropathological hallmark of the disease is the presence of intraneuronal proteinaceous inclusions known as Lewy bodies within the surviving neurons, enriched in filamentous AS. In vitro, dopamine inhibits AS fibril formation, but the molecular determinants of this inhibition remain obsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
127
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(142 citation statements)
references
References 66 publications
11
127
2
2
Order By: Relevance
“…The DA binding site was located in the C-terminal amino acids 127 MPSEE 131 . Indeed binding of DA to AS has been reported near the 125 YEMPS 129 region 59 , which overlaps with the binding site observed by topdown ETD. The localization of M 127 within this region is interesting as it might explain the mechanism by which DA prevents fibril formation and induces DA-dependent oligomerization.…”
Section: Da Binding Is Observed Preferentially With As In Partially Esupporting
confidence: 70%
“…The DA binding site was located in the C-terminal amino acids 127 MPSEE 131 . Indeed binding of DA to AS has been reported near the 125 YEMPS 129 region 59 , which overlaps with the binding site observed by topdown ETD. The localization of M 127 within this region is interesting as it might explain the mechanism by which DA prevents fibril formation and induces DA-dependent oligomerization.…”
Section: Da Binding Is Observed Preferentially With As In Partially Esupporting
confidence: 70%
“…A variety of aromatic molecules such as EGCG [31,50,51], baicalein [52], dopamine [53][54][55], other polyphenols [56], thioflavins [57], curcumin [58][59][60], an anti-PD drug selengiline [61], b-hairpins [62] and many other compounds [63,64] induced formation of mostly disordered a-synuclein oligomers, although in some cases [52] the residual b-structure was found. Many of these compounds were preferentially bound to the C-terminus of a-synuclein [31,62,65]. Addition of EGCG to the preformed b-sheet-rich oligomers did not lead to their disaggregation or loss of secondary structure but did inhibit their interaction with membranes [51].…”
Section: A-synuclein Oligomersmentioning
confidence: 99%
“…Dopamine has previously been shown to inhibit α-Syn fibrillation when used at equimolar ratios. 51 This is thought to occur through hydrophobic interactions with the C-terminus of the protein preventing the formation of mature α-Syn fibrils. However, it was shown that co-incubation of α-Syn with dopamine may give rise to small pre-fibrillar oligomers.…”
Section: A Possible Mechanism Of Toxicitymentioning
confidence: 99%